AVAILABILITY OF THE COMPARATORE METHOD FOR THE FOSSILE SCIURIDAE, DEMONSTRATED WITH AN EXAMPLE OF THE PLEISTOCENE SPERMOPHILUS - POPOVA, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The comparatore method has been applied to the fossil Spermophilus. The intermediate position between the Spermophilus pygmaeus and S. odessanus has been ascertained for the Middle Pleistocene ground squirrel of the Malanchin Potik site. This form shows the pattern of adaptation to the periglacial conditions. The small ground squirrels of Kchalepia site, in spite of their archaical traits, apparently belong to the S. odessanus. The comparatore method is promising for the fossil Sciuridae as a whole.